2003
DOI: 10.1152/ajpregu.00455.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging and caloric restriction on mitochondrial energy production in gastrocnemius muscle and heart

Abstract: Mitochondria are chronically exposed to reactive oxygen intermediates. As a result, various tissues, including skeletal muscle and heart, are characterized by an age-associated increase in reactive oxidant-induced mitochondrial DNA (mtDNA) damage. It has been postulated that these alterations may result in a decline in the content and rate of production of ATP, which may affect tissue function, contribute to the aging process, and lead to several disease states. We show that with age, ATP content and productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
171
3
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(200 citation statements)
references
References 53 publications
20
171
3
1
Order By: Relevance
“…DR attenuates the age-associated increase in rates of mitochondrial ROS generation in multiple tissues and reduces the accrual of oxidative damage [58-61, 87, 88], Mitochondrial function is preserved with age in DR animals, and the loss of mitochondrial membrane fluidity is delayed [89] compared to control animals. Reduction of mitochondrial H 2 0 2 production and oxidative damage to mtDNA in rat gastrocnemius muscle with DR has been described [90] and we have reported that DR in monkeys lowers oxidative damage in skeletal muscle [91]. More recently, the role of ROS has broadened to encompass the control of normal cellular functions (e.g.…”
Section: Stress Oxidative Stress and Longevitymentioning
confidence: 85%
“…DR attenuates the age-associated increase in rates of mitochondrial ROS generation in multiple tissues and reduces the accrual of oxidative damage [58-61, 87, 88], Mitochondrial function is preserved with age in DR animals, and the loss of mitochondrial membrane fluidity is delayed [89] compared to control animals. Reduction of mitochondrial H 2 0 2 production and oxidative damage to mtDNA in rat gastrocnemius muscle with DR has been described [90] and we have reported that DR in monkeys lowers oxidative damage in skeletal muscle [91]. More recently, the role of ROS has broadened to encompass the control of normal cellular functions (e.g.…”
Section: Stress Oxidative Stress and Longevitymentioning
confidence: 85%
“…Some studies report an increased oxidant generation with age [23], whereas others, including Drew and coworkers, using a SSM-enriched preparation, observed no change in mitochondrial oxidant production [24][25][26]. Apparent discrepancies in the extent of age-related changes in mitochondrial oxidant appearance and oxidative stress may reflect the differences in mitochondrial isolation procedures and resultant heterogeneity in the amount of IFM and SSM obtained in sample preparations.…”
Section: Discussionmentioning
confidence: 99%
“…This was independently confirmed by the group of Bruce Ames (Hagen et al 1997). In 2003, it was shown in skeletal muscle that age causes a decrease in ATP content and production by approximately 50% in isolated rat mitochondria (Drew et al 2003). Since the promotion of mitochondriogenesis is critical to prevent aging, an obvious approach was to try and enhance it by physical exercise (Holloszy and Booth 1976;Davies et al 1982).…”
Section: Introductionmentioning
confidence: 92%